Analysis of Stress Distribution on Knife-Edge with Various Occlusion Schemes Using - Jhonson; Chairunnisa, Ricca; Nasution, Ismet Danial (Indonesian Journal of Prosthodontic, 2024)
Edentulism is an oral health problem that has an impact on quality of life because it causes a loss of balance in the stomatognathic system with disruption of mastication. The impaired masticatory function can be exacerbated from knife-edge conditions, thus the masticatory load received by the mucous in the form of stress distribution becomes greater. One of the efforts to reduce stress concentration is to modify the occlusion concept and anatomical shape of the artificial teeth. However, measuring the stress distribution on edentulous mucous with various occlusion schemes was difficult with in vivo and in vitro tests due to inability to represent the complex system of stomatognation. In silico test with A) can be a solution because the modeling simulation is obtained from CT-scan or digital design. This paper discusses the stress distribution analysis on knife-edge condition with various occlusion schemes using FEM. Stress distribution that exceeds the mucous pressure-pain threshold during denture function will cause poor mastication performance. This paper discusses the analysis of stress distribution under knife-edge ridge conditions with various occlusion schemes using FEM. Stress distribution that exceeds the mucous pressure-pain threshold during denture function will cause poor mastication performance. The use of Lingualized or Monoplane occlusion schemes can be a solution because they use semi-anatomical and non-anatomical artificial teeth to reduce the load passed on the cusp and also minimize resistance during lateral movement. The advantages of FEM in obtaining accurate modeling and flexibility in testing allow analyses that are difficult to perform in in vivo and in vitro, FEM measure stress distribution and its relationship with pain on knife-edge ridge base on various occlusion schemes in complete dentures.